The world's fair quilt [large type] - Chiaverini, Jennifer (Chiaverini, Jennifer. Elm Creek quilts novel, 2025)
As fall paints the Pennsylvania countryside in flaming colors, Sylvia Bergstrom Compson is contemplating the future of her beloved Elm Creek Quilts. The Elm Creek Quilt Camp remains the most popular quilter's retreat in the country, but unexpected financial difficulties have beset them and the Bergstrom family's stately nineteenth-century manor. Now in her eighth decade, Sylvia is determined to maintain her family's legacy, but she needs new resources-financial and emotional.